Climate change the insights you need from harvard business review - Review, Harvard Business (Gildan Audio, 2020)
Climate change is threatening our world. How are you responding'Heat waves, flooding, extreme storms, harsh winters. The effects of climate change are only getting worse. How can you ensure your organization is taking the right steps to mitigate this threat-and what can you, as an individual, do to help' These articles by experts and researchers will help you understand how climate change is affecting the future of business. Climate Change: The Insights You Need from Harvard Business Review will prepare you to join in the current discussion, identify immediate and long-term risks for your company, and plan for the future.Business is changing. Will you adapt or be left behind' Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues-blockchain, cybersecurity, AI, and more-each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow.